EFEITO DO ÁCIDO SALICÍLICO NA CONSERVAÇÃO PÓS-COLHEITA DE CEBOLINHA - Candido Panarotto , Victoria; Daniel Pereira Souza , Lucas; Garcia Oliveira , Vitor; Cristina Silva Ribeiro , Fernanda (ANAIS DO ENIC, 2026)
-